2010
DOI: 10.1530/eje-10-0138
|View full text |Cite
|
Sign up to set email alerts
|

Acute exogenous TSH administration stimulates leptin secretion in vivo

Abstract: TSH-receptor (TSHR) has been found in a variety of cell types, including preadipocytes and adipocytes. In vitro, TSH-mediated preadipocyte and adipocyte responses include proliferation, differentiation, survival, and lipolysis. Objective: To measure the response of serum leptin to exogenous administration of recombinant human TSH (rhTSH) in vivo. Patients: One hundred patients with differentiated thyroid cancer already treated by total thyroidectomy and 131 I remnant ablation were enrolled. Mean (GS.E.M.) body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 43 publications
0
39
0
6
Order By: Relevance
“…Another hypothesis is that the association between serum TSH and body weight may be due to leptin (38). In agreement with the leptin hypothesis, a recent study in treated thyroid cancer patient found an increase in serum leptin after acute recombinant human TSH administration, which was proportional to adipose mass (39). Also, the highest correlations in the association between BMI and serum TSH concentration (rZ0.91) was shown among morbidly obese participants (12).…”
Section: Discussionmentioning
confidence: 69%
“…Another hypothesis is that the association between serum TSH and body weight may be due to leptin (38). In agreement with the leptin hypothesis, a recent study in treated thyroid cancer patient found an increase in serum leptin after acute recombinant human TSH administration, which was proportional to adipose mass (39). Also, the highest correlations in the association between BMI and serum TSH concentration (rZ0.91) was shown among morbidly obese participants (12).…”
Section: Discussionmentioning
confidence: 69%
“…A bidirectional interaction is suggested by the intriguing observation that TSH receptors are expressed on adipocytes (52) and that the in vivo administration of recombinant human TSH at supra-physiological doses can induce the release of small but significant amounts of leptin which are proportional to the adipose mass (53). The latter finding confirms that functioning TSH receptors are expressed on the surface of white adipocytes.…”
Section: The Leptin-thyroid Relationshipmentioning
confidence: 77%
“…Potential stimulators of TSH production, explaining the increase in TSH in obese patients, include hormonal mediators of adipose tissue, especially leptin (Rosenbaum et al 2000, Sari et al 2003. Apart from modulating food intake and energy expenditure, leptin acts as a neuroendocrine regulator of the hypothalamic-pituitary-thyroid axis by regulating the expression of TRH in the paraventricular nucleus; leptin secretion by adipose tissue will then be stimulated by TSH (Menendez et al 2003, Oge et al 2005, Feldt-Rasmussen 2007, Santini et al 2010. Leptin may also affect deiodinases, activating the T 4 to T 3 conversion (Zimmermann-Belsing et al 2003, Reinehr 2010.…”
Section: Thyroid Hormonesmentioning
confidence: 99%